Democratic deliberation as a North Star: Showcasing a framework to assess the value for money of systems-change efforts - Peterson, Heidi (Evaluation, 2025)
The growing interest in systems-change initiatives sits alongside increasing pressure to demonstrate value for money (VFM), which is challenging for emergent, interconnected and often intangible work. A new way to assess the VFM of systems-change work involves considering the value of changing system conditions and the creation of potential value for future systems transformation. This innovation combines the Water of Systems Change framework with the Cycles of Value Creation to create five types of value for systems-change work: inherent, potential, applied, realised and transformative. The VFM of systems-change efforts is then best understood, negotiated and judged by different stakeholders through democratic deliberation. A practical case study of WorkWell (a systems-change initiative to improve mental well-being in Victoria, Australia) is used to demonstrate the use of the approach and offer reflections on its rigour.

Using the Participation Cube to Conduct Participation Analysis of Development Projects in Zambia and Uganda - Roberts, Tony; Howard, Jo (The Journal of Development Studies, 2025)
Cooke and Kothari argue that the seductive claims of participation often provide cover for shallow and tokenistic development practices that fail to address unequal power relationships. This paper provides a novel mechanism that documents and enables a three-dimensional analysis of (a) who participates (b) at which project stages and (c) at what level of agency and power. No other mechanism was found in the literature for systematically tracing and analysing changes in power relationship along all three dimensions. The application of this ‘participation tracing’ approach to two case study projects in Zambia and Uganda identified new opportunities to address power inequities thus moving in the direction of what Hickey and Mohan refer to as transformative participation. The method has only been applied retrospectively to date. Further research is necessary applying the method proactively in project planning and during implementation as a form of participatory project assessment.
Keywords: Uganda; Zambia; analysis; cube; evaluation; participation; tracing

Adapting ripple effects mapping for evaluating public health initiatives in complex systems: Reflections and recommendations from seven case studies - Creaser, Amy; Dowling, Lisa; Helme, Zoe; Crowther, Jamie; Casana, Lily; Williams, Rachel; Young, Emma; Nobles, James; Hall, Jennifer (Evaluation, 2025)
Ripple effects mapping is a qualitative and participatory method, developed to capture the dynamic nature and interacting elements of an initiative, and its impacts. We present our experiences of using ripple effects mapping to evaluate complex public health initiatives across seven case studies in Bradford, UK. Seven researchers engaged in qualitative reflective practice to capture their individual experiences of using ripple effects mapping within their research and practice; outlining how the method has been adapted and highlighting key reflections and recommendations for implementing ripple effects mapping in the future. We developed ten recommendations, with corresponding strategies, for implementing ripple effects mapping sessions. The recommendations outline how ripple effects mapping can be implemented to improve engagement and anticipate and overcome potential barriers. In doing so, we outline how ripple effects mapping can be used, and adapted, to evaluate various public health initiatives, in research and practice.

Lost Causal: Debunking Myths About Causal Analysis in Philanthropy - Lynn, Jewlya; Stachowiak, Sarah; Coffman, Julia (The Foundation Review, 2021)

Using a Participatory Theory Driven Evaluation Approach to Identify Causal Mechanisms in Innovation Processes - Blundo‐Canto, Genowefa; Devaux‐Spatarakis, Agathe; Mathé, Syndhia; Faure, Guy; Cerdan, Claire (New Directions for Evaluation, 2020)
Applied agricultural research institutes play different roles in complex agricultural innovation processes, contributing to them with other actors. To foster learning and usable knowledge on how research actions influence such lasting innovation processes, there is a need to identify the causal mechanisms linking these actions and the effects of the changes they enable. A participatory, theory-driven, ex-post evaluation method, ImpresS, was developed by the French Agricultural Research Center for International Development (Cirad). ImpresS reconstructs the innovation history and its impact pathway by analyzing behavioral mechanisms linked to stakeholders' individual reactions and responses, and underlying process mechanisms at a group level. ImpresS relies on iterative updating and refinement and on triangulating data sources and collection methods to ensure internal validity and to increase credibility by enabling different actors to express their viewpoints. Drawing on an in-depth case study, we discuss how ImpresS makes it possible to draw robust conclusions on causal mechanisms while posing challenges linked to the group dynamics and power imbalances commonly encountered in participatory methods. As demonstrated by the case study, ImpresS generates policy-relevant knowledge for future research projects. It also demonstrates how research actions can help coconstruct lasting dynamics that can survive fluctuating institutional support. Distinguishing between behavioral and process mechanisms benefits knowledge use as it makes it possible to disentangle the conditions that trigger changes in a given context while generating research questions concerning the external validity of mechanism hypotheses.

Using Participatory Statistics to Examine the Impact of Interventions to Eradicate Slavery: Lessons from the Field - Oosterhoff, P.; Bharadwaj, S.; Burns, D.; Raj, A. M.; Nanda, R. B.; Narayanan, P. (2016)
This CDI Practice Paper by Pauline Oosterhoff, Sowmyaa Bharadwaj, Danny Burns, Aruna Mohan Raj, Rituu B. Nanda and Pradeep Narayanan reflects on the use of participatory statistics to assess the impact of interventions to eradicate slavery and bonded labour. It deals with: (1) the challenges of estimating changes in the magnitude of various forms of slavery; (2) the potential of combining participatory approaches with statistical principles to generate robust data for assessing impact of slavery eradication; and (3) the practical and ethical questions in relation to working with people living within a context of modern slavery. The paper draws lessons from the realities of using participatory statistics to support the evaluation of a slavery eradication programme in North India.

The journey from rhetoric to reality: participatory evaluation in a development context - Chouinard, Jill Anne; Cousins, J. Bradley (Educational Assessment, Evaluation and Accountability, 2015)
In this paper, we focus on participatory evaluation in the context of international development and specifically on the emerging empirical knowledge base. In a prior review and critique of research on participatory evaluation (Cousins and Chouinard 2012), we examined 121 studies, with only 21 (17 %) situated in development contexts. However, the circumstances and challenges for international development and for development evaluation are distinct from those found in developed countries and therefore warrant separate consideration. To provide a more focused and detailed understanding of participatory evaluation in international development contexts, in this paper we augment our initial sample to a total of 40 studies on participatory evaluation in development published over the past 16.5 years. Based on an analysis of this research and related theoretical and conceptual contributions we identify and discuss eight emergent themes: multiplicity of relationships, consequences of stakeholder selection, characterization of participation, contextual complexity, methodological requirements, cultural influence, politics and power and learning and capacity building. We conclude with some reflections on an agenda for research.

Using Participatory Process Evaluation to Understand the Dynamics of Change in a Nutrition Education Programme - Cornwall, Andrea (IDS Working Papers, 2014)
With roots in approaches to popular education and participatory action research that place the learner and the ‘beneficiary’ of development at the centre of enquiry and action, the participatory visualisation methods associated with Participatory Rural Appraisal have been widely used as tools for learning and accountability. In this article, I reflect on lessons learnt from using these methods in a participatory process evaluation of an educational programme aimed at addressing chronic malnutrition in an East African country. Building on this experience, I explore the educative and empowering dimensions of participatory visualisation methods, and consider the contribution that these methods can make to effective evaluation.
Keywords: Kenya; nutrition; participatory impact evaluation; process evaluation; randomised controlled trials

Three Approaches to Monitoring: Feedback Systems, Participatory Monitoring and Evaluation and Logical Frameworks - Jacobs, Alex; Barnett, Chris; Ponsford, Richard (IDS Bulletin, 2010)
This article compares key attributes, strengths and weaknesses of three different approaches to monitoring development interventions: the logical framework approach, participatory monitoring and evaluation (PM&E) and feedback systems. Academic and practitioner literature describes how logframes meet the needs of senior decision-makers to summarise, organise and compare projects. PM&E meets the needs of field staff to work sensitively with intended beneficiaries and support their learning and empowerment. Feedback systems appear to link the two, providing performance data for managers and creating incentives for implementing staff to focus on their intended beneficiaries. Feedback systems build on the rich heritage of PM&E and are compatible with logframes. They may help provide a manageable and effective approach to accountability that links the means and the ends of development interventions. Feedback systems are at an early stage of development. There is a lot to learn about how and where they work best.

From PRA to PLA and pluralism: practice and theory - Chambers, Robert (IDS, 2007)
PRA (participatory rural appraisal) and the more inclusive PLA (participatory learning and action) are families of participatory methodologies which have evolved as behaviours and attitudes, methods, and practices of sharing. During the 1990s and 2000s PRA/PLA has spread and been applied in most countries in the world. Among the multifarious domains of application, some of the more common have been natural resource management and agriculture, programmes for equity, empowerment, rights and security, and community-level planning and action. Related participatory methodologies which have co-evolved and spread widely as movements include farmer participatory research, Integrated Pest Management, Reflect, Stepping Stones and Participatory Geographic Information Systems. Ideologically and epistemologically PRA/PLA seeks and embodies participatory ways to empower local and subordinate people, enabling them to express and enhance their knowledge and take action. It can be understood as having three main components: facilitators’ behaviours, attitudes and mindsets linked with precepts for action; methods which combine visuals, tangibles and groups; and sharing without boundaries. The interplay of these resonates with theories of chaos, complexity, emergence and deep simplicity, especially self-organising systems on the edge of chaos. Good practice has moved towards an eclectic pluralism in which branding, labels, ownership and ego give way to sharing, borrowing, improvisation, creativity and diversity, all these complemented by mutual and critical reflective learning and personal responsibility. Keywords: participatory methodologies; networks; pluralism; practice; theory.

Participatory evaluation. What is it? Why do it? What are the challenges? - Zukoski, A.; Luluquisen, Mia (Community-based public health policy & practice, 2002)
Yogi Berra was right when he remarked, “If you don’t know where you’re going, you’ll wind up somewhere else.” When we collectively apply our hopes and energies to improving our communities, how do we know if we’re making the right choices along the way? How will we notice when we are spinning our wheels and what changes to make? How will we know that we are making a difference? And how will we know what success looks like to everyone in the group? By taking a community-based public health approach to our work, we create an opportunity to engage in a particular type of evaluation—participatory evaluation – that can help answer those questions. For those groups that are interested in this approach, this policy brief discusses the key concepts of participatory evaluation and some tips for applying it. We also present some real-life examples from two evaluators who work with grantees of the Partnership for the Public’s Health Initiative.

PRA five years later - where are we now? / DRP - Cinco años después, ¿dónde nos encontramos? - Chambers, Robert; Guijt, Irene (Forest, Trees and People Newsletter, 1995)
PRA five years later: where are we now?

Learning and not learning from experience in rural project planning - Hulme, David (Public Administration and Development, 1989)
The theme of learning from experience as a means of improving the effectiveness of rural development projects and programmers has been common in recent years. Considerable effort has been put into refining, monitoring and evaluation systems to enhance organizational learning processes. However, an emphasis on normative approaches to evaluation and learning from experience has led to the neglect of research into the actual processes by which rural development agencies utilize experience. The case study presented here points to the shortcomings of such approaches and illustrates the partisan manner in which individuals and organizations treat the lessons of experience. Actively ‘not learning from experience’ is as much a part of organizational processes as learning from experience. This paper examines the implications of this finding and reviews alternative approaches to improving experiential learning in rural development activities. It is found that such a perspective does not generate the innocuous technical prescriptions characteristic of conventional approaches, but a number of useful directions for further research can be identified.